Road Accident Analysis and Safety Audit: A Case Study of MDR 132 - Khan, Amir Ali; Sabir; Dass, Sachin; Singh, Gyanendra; Jaglan, Saurabh (Communications - Scientific Letters of the University of Zilina, 2023)
Road accident and road safety are the key global concerns and problem for emerging nations like India. It has been attempted to examine the accidents that happened on Major District Road (MDR) 132 (Nuh to Hodal), India in the last five years. The primary objective of this study was to perform the Road Safety Audit for identification of accident-prone areas based on Accident Severity Index (ASI) and provide some improvement measures in order to lower the frequency and severity of accidents. Identified accident prone locations (blackspots) were ranked according to the ASI index. The distribution of accidents based on various parameters were also discussed. Site visit of critical sections of the road to observe road deficiencies were made and safety recommendations, along with the risk associated with them and priority as per IRC: SP: 88-2019, were suggested.
Keywords: accident prone location; accident severity index (ASI); road safety audit; severity; nature of accident